Cardiovascular risk profiles in a lupus cohort: what do different calculators tell us?. Issue 1 (28th July 2017) - Boulos, Daniel; Koelmeyer, Rachel L; Morand, Eric F; Hoi, Alberta Y
Abstract : Background: Cardiovascular disease (CVD) is the leading cause of death worldwide and this risk is increased in patients with SLE who may not conform to traditional cardiovascular risk profiles. Aims: To determine the prevalence of high CVD risk among patients with SLE calculated using different risk calculators, and to characterise those identified as high risk. Methods: A cross-sectional analysis to estimate CVD risk using the Framingham Risk Equation (Framingham score) and an SLE-specific CVD risk equation (SLE score) was undertaken using data from a single centre cohort. The characteristics of patients identified as 'high risk' by the SLE score only (the 'missed group') were compared with those identified by the Framingham score (the 'conventional group'). Results: 146 patients were included; 22 (15%) and 44 (30%) were determined to be at 'high risk' based on the Framingham and SLE scores, respectively. Patients in the 'missed group' were less likely to have traditional risk factors and were more likely to be female (81% vs 50%; p=0.03), younger (mean age 54 vs 69 years p<0.01) and have lower systolic blood pressure (132 vs 143 mm Hg; p=0.05). Of those deemed high risk, only a minority were treated to target blood pressure and lipid levels. Conclusions: A large proportion of patients with SLE could be re-classified as high risk using a formula that incorporates SLE disease-related parameters. These patients have different profiles to those identified using a conventional risk model. Optimal CVD risk assessment and management warrants further attention in SLE.